The Influence of Principal Leadership, Organizational Culture and Work Motivation on Teacher Performance at Public Elementary Schools in Kapanewon Prambanan - Anang Nugroho; Suyud Suyud (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study examined the effects of principal leadership, organizational culture, and work motivation on teacher performance in public elementary schools in Prambanan District, Sleman, Special Region of Yogyakarta, Indonesia. A quantitative approach with a multiple linear regression design was employed. The sample consisted of 133 teachers selected using cluster random sampling, with the sample size determined through the Slovin formula. Data were collected using a Likert-scale questionnaire. The research instrument was validated through expert judgment in educational management and demonstrated adequate internal consistency reliability. Data analysis included prerequisite tests of normality, linearity, and multicollinearity, followed by hypothesis testing using SPSS. The findings revealed that principal leadership had a positive and significant effect on teacher performance (t = 2.644, p = 0.009), organizational culture had a positive and significant effect (t = 2.151, p = 0.033), and work motivation had the strongest positive and significant effect (t = 7.178, p < 0.001). Simultaneously, the three independent variables significantly influenced teacher performance (F = 51.086, p < 0.001). The coefficient of determination (R² = 0.543) indicated that principal leadership, organizational culture, and work motivation explained 54.3% of the variance in teacher performance. Further contribution analysis showed that work motivation made the largest contribution (37.8%), followed by principal leadership (9.9%) and organizational culture (6.5%). These findings suggest that improving teacher performance requires strengthening school leadership, developing a supportive organizational culture, and prioritizing strategies to enhance teacher work motivation